Templates of smart specialisation: Experiences of place-based regional development strategies in Germany and Austria - Elisabeth Baier; Henning Kroll; Andrea Zenker (Fraunhofer Institute for Systems and Innovation Research ISI, 2013)
[Introduction] The notion of 'smart specialisation' is set to become an important policy rationale in the upcoming structural funding period 2014-2020. Although the original academic concept of this policy approach was sectorally oriented and rooted in the analysis of the EU-US productivity gap (e.g. Foray et al. 2009), the concept is increasingly applied to regional contexts. Essential for the application of the smart specialisation concept in a regional context is the fact that regions are often faced with scarce resources and limited budgets which they should allocate according to external influences (e.g. global competition) and inherited structures (sectoral foci, linkages between sectors, innovation infrastructure). Therefore, and in accordance with the smart specialisation strategy (S3), regional governments need to design policies in such a way as to support the most promising areas of present and future comparative advantage in order to foster regional prosperity. Although the ideas behind smart specialisation are not entirely new on the regional level, the smart specialisation concept is going to expand its influence to regional innovation policy making. Thus, this contribution illuminates the interface between the smart specialisation concept and regional systems of innovation approach, since innovation is going to be a key issue in the next structural funding period. Key arguments for the usefulness of the smart specialisation concept in the field of the design of regional innovation policy making will be collected and three examples are presented in form of case studies. This contribution aims to demonstrate that the principles of smart specialisation have been implicitly applied in certain European regions for years in form of future-oriented transformation processes. Likewise this contribution aims to illustrate how the experiences from these regions can contribute to policy learning. In doing so, the structure is the following: firstly, existing literature on the smart specialisation concept is revised and secondly, these findings are reconsidered with regard to the regional systems of innovation approach. In particular, if and how the smart specialisation concept will influence regional development processes and potentially regional innovation systems. Three key working theses adopt these ideas and guide the empirical analyses. Methodologically, the paper pursues a case study approach. The policy trajectories of three different case study regions are analysed within the innovation systems approach and conclusions are drawn concerning the smart specialisation concept. Finally, the paper closes with a conclusion, concerning the influencing potential of the smart specialisation concept on regional innovation systems.
Keywords: 330